Issues in Fintech Regulation: What can Peru learn from other countries? - Coloma, Maria Gabriela (Technium Social Sciences Journal, 2020)
Today, Peru is witnessing an exponential growth in Fintech, both in number local start-ups being founded and international scale-ups arriving to the country. However, the lack of government regulation on the topic slows down the growth of Fintech because it depletes such industry of consumer and investor confidence. This research aims to explore what regulatory framework Peru should adopt as a response to the unstoppable growth in Fintech within the nation. The study takes a comparative approach, analyzing Fintech regulation in three different countries: Mexico, Brazil and the United Kingdom. The study finds that Peru should follow Brazil´s footsteps in enacting strong, detailed and strict regulation which will result in improving local consumer trust and in attracting foreign investment into the Peruvian Fintech industry. Plus, the study suggests that Peru should centralize Fintech regulation with one single authority, such as the Financial Conduct Authority in the case of the United Kingdom.